Scale of Family Unpredictability During Childhood: Validity Evidence - Howat-Rodrigues, Anna Beatriz Carnielli; Tokumaru, Rosana Suemi (Paidéia (Ribeirão Preto), 2014)
The aim of this study was to examine evidence of validity for the Brazilian version of the Scale of Family Unpredictability during childhood. A total of 740 people participated in the study. The first sample was composed of 121 women over 40 years of age (Xage = 5.86), 157 adults in conflict with the law (148 men, Xage = 34.20), and 251 college students (122 men, Xage = 19.60). The second sample included 211 college students (90 men, Xage = 21.53). Exploratory and confirmatory analysis indicated that the three-dimensional model (nurturance, money, meals) presented a better goodness of fit, with satisfactory reliability indexes. A significant effect of all unpredictability factors on the purchasing power of the participants was found, confirming validity by contrasting groups of EIFI: people belonging to socioeconomic classes with lower purchasing power presented higher family unpredictability during childhood. We concluded that the three-dimensional EIFI is psychometrically adequate, allowing the differentiation of groups in the constructs evaluated.